Economic profitability of yellow passion fruit in organic cultivationunder different input levels and irrigation - Lemos Uchoa, Thays; Elviro de Araújo Neto, Sebastião; de Moura Francisco, Wagner; Mendes da Silva, Nilciléia; de Souza e Souza, Luís Gustavo; Penha Pinto, Geazí (Comunicata Scientiae, 2021)
The productivity of passion fruit is low compared to its productive potential which in organic system is due to rainfed cultivation and low input levels. The aim of this work was to evaluate the profitability of yellow passion fruit production in organic system under different input levels and irrigation. The experiment was carried out in Rio Branco - AC, at the Seridó Ecological Site, conducted from November 2016 to August 2018. Randomized block design was used, arranged in a factorial scheme (3x2) with four replicates. The factors evaluated were: three input levels of inputs (fertilizers and alternative pesticides) and presence or absence of irrigation. Fertilization was carried out based on the nutrient content of the soil analysis and according to the yield estimate 5 t ha-1, 10 t ha-1 and 15 t ha-1. The irrigation used was with a micro sprinkler per plant. The production cost, profitability, simplified economic analysis, production for total and operating coverage were calculated based on capital depreciation, input level and labor during two cultivation years. The highest input level and irrigation increase productivity, total revenue and production requirements to cover total and operating costs. Fixed cost is higher when using combination of irrigation and input level 1; however, it provided positive economic yields.